Why Asymptomatic COVID19 Patient Could Face a Sudden Death - Zaher, Amr; Ali, Sara (International Journal of Innovative Research in Medical Science, 2021)
Since the novel SARS-COV 2 has emerged from its inception in December 2019 till November 2020 about 68,587,138 infected cases,47,482,639 recovered, and 1,563,468 deaths [1,2]. Most of the death cases were diagnosed with critically ill pneumonia correlated with acute respiratory distress syndrome (ARDS) [2]. All of the previous numbers mostly have been recorded based on the patients who displayed symptoms whether from the most common symptoms like fatigue, cough, fever or severe symptoms as trouble breathing, persistent pain, or pressure in the chest. However, there are many infected people but didn’t show any symptoms although they were developing COVID 19 complications, and some of them even died before know that they had a COVID 19. This is one of the most mysterious actions of coronavirus and bewildered the physicians how the patient could lose his oxygen gradually without panting to catch up his breath. In other words, asymptomatic patients who look completely fine don’t necessarily far from the risk; they perhaps internally suffer from silent hypoxia or lung damage.